Chapter 5: 'Target Suitability and the Crime Drop' from book: The Criminal Act: The Role and Influence of Routine Activity Theory - Farrell, Graham (Palgrave Macmillan, 2015)
This chapter is open access under a CC BY license. It is from The Criminal Act: The Role and Influence of Routine Activity Theory, edited by Martin A. Andresen and Graham Farrell. The full volume provides a unique collection of essays in honour of the work of Marcus Felson and his notable contribution to routine activity theory, environmental criminology and the discipline more broadly.